Heat Transfer and Flow Characteristics of Coal Slurries under the Temperature Difference between Inside and Outside of the Channel - Liu, Yang; Hu, Xintao; Gao, Feng; Gao, Yanan (Applied sciences, 2022)
The pipeline transportation of coal slurries is always subject to a temperature difference between the outdoors environment and the fluid body. As slurries’ viscosity is typically temperature dependent, the flow is accompanied by the heat transfer. In this study, we used the CFD method to investigate temperature distributions and flow structures in straight and curved channels, which has not previously been investigated, according to our knowledge. First, the results demonstrate that the cooling process influences the flow structures along the stream. The fluid turns more sharply in the cooler fluid in the curved channel, the streamlines overlap at an earlier position within the bend, and the velocity maximum zone is wider. Cooling also has a significant impact on transverse flow. Because of the higher viscosity of the more cooled fluid and thus the difficulty of shearing the fluid in the stream-wise direction, the vorticity and strength of the vortex flow are greater. The fluid velocity at the central part of the channel points toward the inner wall at the beginning of the bend, resulting in an inner-wall biased temperature distribution, as the heat transfer is partially carried out by the fluid velocity. The central velocity points toward the outer wall at the end of the bend, resulting in the outer-wall biased temperature profile.